Assessment of study space usage in the Kenneth Dike Library (2017)
This paper explores the actual use of the physical space in Kenneth Dike Library by the students’ population, the role these spaces are playing for learning and for related services in the university of Ibadan academic environment. It looked at the suitability of available spaces and suggestions for improvement. Survey method was adopted for the study with 94.5% response rate. It found that quite study space is what attracts majority respondents to Kenneth Dike Library. What emerged was that academic pursuits remain the most common activities in the library space.